(untitled) (Docentes 2.0 Journal, 2021)
The concepts of peace, coexistence, conflict have taken on in some social settings, including the educational one, an indiscriminate use, disuse, and implementation. For this reason, the research work conciliation tables were a proposal for the formation of peace and coexistence, from the mediation and transformation of conflicts, it was born by observing the handling of disputes by students of grade 701 (17 girls, 23 children) belonging to the Monsignor Jaime Prieto Amaya educational institution. The objective developed and achieved consisted of analyzing the importance of the conciliation tables as a pedagogical strategy for the mediation of conflicts, training in peace, and coexistence from conflict transformation theory. A qualitative methodology was used, with an action research approach that will download the necessary information to identify the notions of the critical concepts of the work, propose, design, and execute the strategy of the conciliation tables. As the process results are conducted in the students, in any conflict situation, they developed a conciliation table to understand the real reasons for the positions of the events and establish themselves, the mechanisms of resolution and non-repetition. In this sense, the conciliation and conflict transformation tables’ proposal are a natural and concrete bet for the construction of direct peace. Children and young people discover, learn, and transmit a way to regulate conflicts in a non-violent way and reinforce their integral formation.